2020
DOI: 10.1177/0003134820954821
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neoadjuvant Versus Adjuvant Therapy for Duodenal Adenocarcinoma: A National Cancer Database Propensity Score Matched Analysis

Abstract: Introduction Adjuvant therapy is recommended in duodenal adenocarcinoma (DA), but the role of neoadjuvant therapy remains undefined. We compared the effect of neoadjuvant therapy to adjuvant therapy on overall survival, 30-day, and 90-day mortality following the resection of DA. Methods A retrospective review of the National Cancer Database was performed on patients with DA who received either adjuvant or neoadjuvant therapy in addition to surgical resection. Propensity score matching was done for patient, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the last decade, the diagnosis of epithelial neoplasia of the duodenum has been increased by endoscopic examination in Japan; therefore, the development of this diagnostic tool is considered to be a reason for increased findings [4] , [5] , [6] , [7] . Regardless, according to finding DC at an earlier stage that can be locally located in the duodenum, radical surgery seems to be more frequent than in previous periods according to reports and our experiences [1] , [2] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . In fact, our present series of nine patients showed that the first curative case was found in 2014; therefore, preliminary evaluation of surgical treatment for DC was examined in this report.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the last decade, the diagnosis of epithelial neoplasia of the duodenum has been increased by endoscopic examination in Japan; therefore, the development of this diagnostic tool is considered to be a reason for increased findings [4] , [5] , [6] , [7] . Regardless, according to finding DC at an earlier stage that can be locally located in the duodenum, radical surgery seems to be more frequent than in previous periods according to reports and our experiences [1] , [2] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . In fact, our present series of nine patients showed that the first curative case was found in 2014; therefore, preliminary evaluation of surgical treatment for DC was examined in this report.…”
Section: Discussionmentioning
confidence: 79%
“…In this series, we attempted to perform bowel anastomosis with surgical ingenuity, as shown above. Although we reported nine cases, a cohesive cohort study has not yet been fully collected [9] , [10] , [11] . Nationwide or international cohort studies at multiple cancer institutions are expected.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation